2022
DOI: 10.3390/pharmaceutics14020328
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme Assays to Quantify the Capping Efficiency of In Vitro-Transcribed mRNA

Abstract: The presence of the cap structure on the 5′-end of in vitro-transcribed (IVT) mRNA determines its translation and stability, underpinning its use in therapeutics. Both enzymatic and co-transcriptional capping may lead to incomplete positioning of the cap on newly synthesized RNA molecules. IVT mRNAs are rapidly emerging as novel biologics, including recent vaccines against COVID-19 and vaccine candidates against other infectious diseases, as well as for cancer immunotherapies and protein replacement therapies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…It has been reported recently that ribozyme-cleaved 5’ cleavage fragments of in vitro transcript could be enriched for LC-MS analysis using silica-based spin columns. The spin column format, however, requires 20 – 60 μg RNA input (Vlatkovic et al 2022). The use of RNase H and biotinylated targeting oligos allows for affinity enrichment (Beverly et al 2016) that could potentially decrease the input RNA requirement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported recently that ribozyme-cleaved 5’ cleavage fragments of in vitro transcript could be enriched for LC-MS analysis using silica-based spin columns. The spin column format, however, requires 20 – 60 μg RNA input (Vlatkovic et al 2022). The use of RNase H and biotinylated targeting oligos allows for affinity enrichment (Beverly et al 2016) that could potentially decrease the input RNA requirement.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical methods such as gel-electrophoresis and mass spectrometry may lack the resolution or detection range to confidently distinguish between Cap-1 or Cap-0 capped RNA and unreacted or intermediate capping products on full-length synthetic mRNA molecules. To overcome this problem, methods that cleave a pre-defined fragment from the 5’ end of the mRNA molecule using custom designed DNAzyme (Cairns et al 2003), ribozyme (Vlatkovic et al 2022) or DNA-RNA chimera-guided RNase H (Lapham and Crothers 1996; Yu et al 1997; Lapham et al 1997) have been reported. The 5’ cleavage fragments, ranging from 5 to 30 nucleotides long, can be readily analyzed by denaturing gel electrophoresis or liquid chromatography-mass spectrometry (LC-MS) (Beverly et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical methods such as gel electrophoresis and mass spectrometry may lack the resolution or detection range to confidently distinguish between Cap-1 or Cap-0 capped RNA and unreacted or intermediate capping products on full-length synthetic mRNA molecules. To overcome this problem, methods that cleave a predefined fragment from the 5′ end of the mRNA molecule using custom designed DNAzyme ( Cairns et al 2003 ), ribozyme ( Vlatkovic et al 2022 ), or DNA–RNA chimera-guided RNase H ( Lapham and Crothers 1996 ; Lapham et al 1997 ; Yu et al 1997 ) have been reported. The 5′ cleavage fragments, ranging from 5 to 30 nt long, can be readily analyzed by denaturing gel electrophoresis or liquid chromatography-mass spectrometry (LC-MS) ( Beverly et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%